EuMIXFOR Introduction: integrating scientific knowledge in sustainable management of mixed forests - Bravo-Oviedo, Andres; Barreiro, Susana; Strelcova, Katarina; Pretzsch, Hans (Forest Systems, 2014)
No abstract